The new economic governance arrangements and autonomous collective bargaining in the European Union - Willi Koll (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
The current crisis in the Economic and Monetary Union (EMU) was caused by strong divergences in wages, unit labour costs and prices resulting in member states running large current account surpluses and deficits. The European Council attempted to respond to this governance gap by adopting a regulation on the prevention and correction of macroeconomic imbalances which, however, is asymmetric and hence itself imbalanced. By adopting the regulation, governments committed themselves to safeguarding a balanced development of unit labour costs, and hence of wages, which however are the responsibility of independent social partners, creating a so far unresolved tension. In order to address this shortcoming, this study describes a number of options. The option, which here is considered first best, advocates stronger centralization and coordination of the wage-setting process, underpinned by counter-cyclical fiscal policy and an effective competition policy. As means to implement the greater coordination implied by this option, in addition to the already existing Macroeconomic Dialogue at European level, a special Macroeconomic Dialogue on national level as well as on EMU level is called for.
urn:nbn:de:101:1-2014031112548
Keywords: 330